Gambaran Pemetaan dan Pencemaran Lingkungan dari Dokumen Upaya Pengelolaan Lingkungan (UKL) dan Upaya Pemantauan Lingkungan (UPL) Klinik Berdasarkan Potensi Pencemaran di Kabupaten Jombang - Anggara Widyartanto; Lilis Sulistyorini; Muhammad Rosyid Ridlo (Universitas Airlangga, 2023)
Background: Clinical activities are activities that can produce various wastes in the form of liquid, solid and gas. Clinics will not only produce ordinary waste, but also infectious waste and other medical waste that can cause health problems which are a source of disease transmission. Management of clinical B3 waste is very important, because if B3 waste is not properly managed, various impacts can arise, namely: environmental pollution, causing injury, and nosocomial diseases. Objectives: This internship activity aims to analyze the mapping and environmental pollution description from the clinical UKL-UPL environmental document based on the potential for pollution in the Jombang DLH. Methods: The implementation methods used include online discussion, online assessment, participation, and literature study. The instrument used in data collection in the implementation of the internship is the draft UKL- UPL environmental document for the Jombang DLH Environmental Impact Study. Results: Data for UKL-UPL clinics registered by DLH Jombang is 12% or 80 clinical institutions. The mapping of the coordinates of the clinics in Jombang Regency illustrates the even distribution of clinical institutions and it can be seen that the majority of clinics in Jombang Regency are concentrated in Jombang District, which consists of clinics that produce 2 types of waste and clinics that produce 3 types of waste. From the map it can be seen that the sub-districts that have the least number of clinics are Wonosalam, Bareng, and Ngusikan sub-districts. Conclusions: The majority of clinics in Jombang Regency are concentrated in Jombang District, which consists of clinics that produce 2 types of waste and clinics that produce 3 types of waste.